Grass-root preparedness against potential flood risk among residential and commercial property holders. Issue 1 (9th February 2015) - Jerry Velasquez, Dr; Mis, Namrata Bhattacharya; Joseph, Rotimi; Proverbs, David; Lamond, Jessica
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to investigate the level of preparedness among property owners who had experienced flood damage to their properties in two cities in England following the summer floods of 2007. Flooding can have a variety of impacts on residential properties and businesses that may be unprepared and therefore vulnerable to both direct and indirect effects. Research suggests that the focus in analysis of damage to flood plain population (residential and commercial) tends to be on the direct tangible impacts, limiting their ability to recognize the true costs of flooding, thereby leading to unpreparedness to future flooding. Greater understanding of the level of preparedness against different types of flood impacts is likely to contribute towards increased knowledge of the likely resilience of residential and commercial property occupiers. Design/methodology/approach – Primary data obtained through self-administered postal questionnaire survey of floodplain residential and commercial residents provide the basis for the research analysis and findings. The rationale behind choosing the locations for the research was based on the need to investigate areas where a sizeable number of residential and commercial properties were affected during the 2007 event, in this case, Sheffield and Wakefield in the northern part of England were chosen. The data collected were subjected to descriptive statistical analysis. Findings – The result of the analysis revealed that non-structural measures have been implemented by more people when compared to other measures, which can be linked to the fact that non-structural measures, in most, cases do not have financial implication to the property owners. The uptake of the other measures (resistance and resilience) is very low. It can be concluded from the findings that the level of implementation of measures to reduce damage from potential future flooding among the flood plain residents is relatively low and mainly focussed towards reducing the direct effects of flooding. Practical implications – The study argues that increased resilience can be sustainable only by developing integrated attitude towards risk reduction not only by enhancing coping strategy by reducing direct impacts of flooding but also equally focussing on indirect effects. Originality/value – There have been previous studies towards investigating the impacts of flooding on residential and commercial property owners as a separate entity. It is believed that this is the first time in which both residential and commercial properties will be investigated together as one body of research.